Effect of cold expansion on improving of fatigue initiation life in Aluminium alloy (Fracture and Structural Integrity, 2018)
In this paper, numerical investigation was carried out to quantify the effect of the cold expansion on fatigue crack initiation in Aluminium alloy. The improvement in fatigue initiation life of specimen after the cold expansion process was investigated with the drilled hole of 2024 T351 Aluminium alloy plate. The 4.6 % in degree of expansion is applied witch is associated with the effect of friction (µ=0.2). Residual stress field is determined using 3D Finite Element Analysis and shows the presence of compressive residual stress around the hole. The results showed a high level of compressive residual stress in mild and exit face of hole. Local strain approach is applied in evaluation of fatigue initiation lives under Afgrow environment code. Fatigue initiation lives are improved by the presence of compressive residual and comparatively to the drilled hole. Moreover, increasing in stress ratio, increases the fatigue initiation lives with and without the presence of compressive residuals stresses
Keywords: Fatigue crack initiation; Cold expansion; Compressive residual stress; Stress ratio; Aluminium alloy